Sosialisasi Peluang Bisnis Budidaya Maggot BSF Pada Masyarakat Pondok Dalem Semboro Jember - Abidin, Asroful; Sadiq, Aefra Belladena; Wim, Setyo; Malatania, Lala Arum (SEJAGAT : Jurnal Pengabdian Masyarakat, 2024)
In facing the era of environmental uncertainty and the need for sustainable solutions, Black Soldier Fly (BSF) maggot cultivation has emerged as a promising alternative. The business potential of BSF maggots presents opportunities for communities in Pondok Dalem, Semboro, Jember, and various parts of the world. Socialization approach becomes crucial in integrating sustainable practices into daily life. BSF larvae bring innovation in organic waste management, reducing the burden on Landfills. However, awareness of the significant amount of organic waste disposed of remains low in society. The socialization approach involves preparation, im-plementation, and evaluation, utilizing pretest and posttest methods to measure participants' knowledge improvement using the n-gain calculation. The evaluation results show the effectiveness of socialization, with a mean n-gain score reaching 76.904%. It is hoped that this approach can continue to be utilized to expand its positive impact on local environments and economies and to in-troduce sustainable practices to communities at large. Thus, the use of socialization in introducing BSF maggot cultivation not only benefits the environment but also creates sustainable business opportunities and empowers community economies.